Acceptance Remarks. (2021) - McDonald, Gabrielle Kirk
Abstract : I remember attending a Women in International Law Interest Group (WILIG) luncheon many years ago when we all fit in the small breakfast room at the Fairmont Hotel in Washington, D.C. Now, WILIG luncheons at the ASIL Annual Meeting are sold out! If you do not buy your ticket early, you are out of luck! I believe this popularity is due not only to the increase in the number and influence of women in international law, but also is a show of appreciation for the role of WILIG in this growth.